Licenciamento compulsório da patente de medicamentos e os parâmetros para remuneração do titular da patente - Silva, Cinthya Nunes Vieira da (2025)
This research analyzes the criteria for determining the remuneration due to the patent holder in cases of compulsory licensing of drug patents. The research addresses the tension between the protection of industrial property, the incentive for innovation, and the realization of the fundamental right to health, highlighting the insufficiency of the current normative parameters in the Industrial Property Law (Law No. 9,279/96) to determine "adequate remuneration," which generates legal uncertainty. Through bibliographic and documentary research, based on the logical-systematic method, the national and international regulatory framework, doctrine, jurisprudence, and foreign law experiences are examined. The compulsory licensing of the antiretroviral drug Efavirenz in 2007 is analyzed as a central case study, in which remuneration was set at 1.5% based on international parameters, revealing an ad hoc solution in the absence of a consolidated methodology. It is concluded that the Efavirenz experience, combined with the analysis of legal criteria and international practices, can serve as a paradigm for constructing a multifactorial methodological roadmap to provide predictability and legitimacy for setting royalties in future licensing cases, balancing public interest with fair compensation for the patent holder.